Coupling Glucose Dehydrogenation with CO2 Hydrogenation by Hydrogen Transfer in Aqueous Media at Room Temperature. Issue 13 (1st June 2018) - Ding, Guodong; Su, Ji; Zhang, Cheng; Tang, Kan; Yang, Lisha; Lin, Hongfei
Abstract: Conversion of CO2 into value‐added chemicals and fuels provides a direct solution to reduce excessive CO2 in the atmosphere. Herein, a novel catalytic reaction system is presented by coupling the dehydrogenation of glucose with the hydrogenation of a CO2 ‐derived salt, ammonium carbonate, in an ethanol–water mixture. For the first time, the hydrogenation of CO2 to formate by glucose has been achieved under ambient conditions. Under the optimal reaction conditions, the highest yield of formate reached approximately 46 %. We find that the apparent pH value in the ethanol–water mixture plays a central role in determining the performance of the hydrogen‐transfer reaction. Based on the 13 C NMR and ESI–MS results, a possible pathway of the coupled glucose dehydrogenation and CO2 hydrogenation reactions was proposed. Abstract : RT conversion : A novel catalytic reaction system is presented by coupling the dehydrogenation of glucose with the hydrogenation of a CO2 ‐derived salt in an ethanol–water mixture at room temperature. Based on the 13 C NMR and ESI–MS results, a possible mechanism is also proposed.